A thermally regenerative ammonia-based battery for efficient harvesting of low-grade thermal energy as electrical power. Issue 1 (25th November 2014) - Zhang, Fang; Liu, Jia; Yang, Wulin; Logan, Bruce E.
Abstract : A thermally regenerative ammonia-based battery that was driven by metal ammine complex formation and ammonia concentration gradients to create voltage, showed efficient conversion of low-grade thermal energy into electrical power. Abstract : Thermal energy was shown to be efficiently converted into electrical power in a thermally regenerative ammonia-based battery (TRAB) using copper-based redox couples [Cu(NH3 )4 2+ /Cu and Cu(ii )/Cu]. Ammonia addition to the anolyte (2 M ammonia in a copper-nitrate electrolyte) of a single TRAB cell produced a maximum power density of 115 ± 1 W m −2 (based on projected area of a single copper mesh electrode), with an energy density of 453 W h m −3 (normalized to the total electrolyte volume, under maximum power production conditions). Adding a second cell doubled both the voltage and maximum power. Increasing the anolyte ammonia concentration to 3 M further improved the maximum power density to 136 ± 3 W m −2 . Volatilization of ammonia from the spent anolyte by heating (simulating distillation), and re-addition of this ammonia to the spent catholyte chamber with subsequent operation of this chamber as the anode (to regenerate copper on the other electrode), produced a maximum power density of 60 ± 3 W m −2, with an average discharge energy efficiency of ∼29% (electrical energy captured versus chemical energy in the starting solutions). Power was restored to 126 ± 5 W m −2 through acid addition to the regenerated catholyte to decrease pH and dissolve Cu(OH)2 precipitates, suggesting that an inexpensive acid or a waste acid could be used to improve performance. These results demonstrated that TRABs using ammonia-based electrolytes and inexpensive copper electrodes can provide a practical method for efficient conversion of low-grade thermal energy into electricity.